Microstructure-dependent mechanical properties of electrospun core–shell scaffolds at multi-scale levels. (June 2016) - Horner, Christopher B.; Ico, Gerardo; Johnson, Jed; Zhao, Yi; Nam, Jin
Abstract: Mechanical factors among many physiochemical properties of scaffolds for stem cell-based tissue engineering significantly affect tissue morphogenesis by controlling stem cell behaviors including proliferation and phenotype-specific differentiation. Core–shell electrospinning provides a unique opportunity to control mechanical properties of scaffolds independent of surface chemistry, rendering a greater freedom to tailor design for specific applications. In this study, we synthesized electrospun core–shell scaffolds having different core composition and/or core-to-shell dimensional ratios. Two independent biocompatible polymer systems, polyetherketoneketone (PEKK) and gelatin as the core materials while maintaining the shell polymer with polycaprolactone (PCL), were utilized. The mechanics of such scaffolds was analyzed at the microscale and macroscales to determine the potential implications it may hold for cell-material and tissue-material interactions. The mechanical properties of individual core–shell fibers were controlled by core–shell composition and structure. The individual fiber modulus correlated with the increase in percent core size ranging from 0.55±0.10 GPa to 1.74±0.22 GPa and 0.48±0.12 GPa to 1.53±0.12 GPa for the PEKK–PCL and gelatin-PCL fibers, respectively. More importantly, it was demonstrated that mechanical properties of the scaffolds at the macroscale were dominantly determined by porosity under compression. The increase of scaffold porosity from 70.2%±1.0% to 93.2%±0.5% by increasing the core size in the PEKK–PCL scaffold resulted in the decrease of the compressive elastic modulus from 227.67±20.39 kPa to 14.55±1.43 kPa while a greater changes in the porosity of gelatin-PCL scaffold from 54.5%±4.2% to 89.6%±0.4% resulted in the compressive elastic modulus change from 484.01±30.18 kPa to 17.57±1.40 kPa. On the other hand, the biphasic behaviors under tensile mechanical loading result in a range from a minimum of 5.42±1.05 MPa to a maximum of 12.00±1.96 MPa for the PEKK–PCL scaffolds, and 10.19±4.49 MPa to 22.60±2.44 MPa for the gelatin-PCL scaffolds. These results suggest a feasible approach for precisely controlling the local and global mechanical characteristics, in addition to independent control over surface chemistry, to achieve a desired tissue morphogenesis using the core–shell electrospinning. Graphical abstract: Highlights: Core–shell electrospinning systematically produces mechanically distinctive fibers. Modulus of individual core–shell electrospun fiber follows the rule of mixtures. Compressive modulus of scaffold based on such fibers depends on its porosity. Tensile modulus of scaffold depends on both fiber modulus and scaffold porosity.